Technology Acceptance of the OKY Application Among Junior High School Girls in Indonesia: A Tam-Based Study - Muthmainnah, Muthmainnah; Wulandari, Elvia Alif; Siswantara, Pulung; Salsabila, Annisa Clara; Restuti, Dini Yulia; Qariati, Nurul Indah; Islam, Achmad Syaiful (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2025)
Introduction: Adolescents experience significant physical changes during puberty; however, many lack adequate knowledge regarding menstrual hygiene management. This knowledge gap can lead to negative health outcomes. The OKY application is a menstrual tracker that also provides an encyclopedia on puberty and menstrual hygiene, and offers valuable educational resources. Despite its potential, the application remains underutilized by adolescents. This study aims to analyze the relationship between technology acceptance variables and the use of the OKY application among junior high school students. Methods: This study employed a cross-sectional design. Data were collected from 72 female junior high school students who had been introduced to the OKY application. Participants were selected using proportionate stratified random sampling. The Technology Acceptance Model (TAM) was utilized to assess user perceptions through a structured questionnaire. TAM was utilized innovatively to assess students' perceptions of the application's ease of use, usefulness, and intention to use through a structured questionnaire specifically tailored for this educational setting. Data analysis was conducted using the Spearman correlation test to evaluate relationships among variables. Instrument validation and ethical approval were secured in accordance with research ethics guidelines. Result: The study revealed a strong correlation between knowledge, skill, and curiosity with perceived usefulness of the OKY application. Furthermore, significant relationships were identified between perceived ease of use, attitude toward using, behavioral intention, and actual system use. These findings indicate that both cognitive and affective factors influence the adoption of the application. Conclusion: To enhance the adoption and effective use of the OKY application for menstrual hygiene management, it is recommended to strengthen socialization initiatives and implement peer counseling programs. Such interventions may support increased awareness, acceptance, and consistent use of the application among adolescents.